Early-Life Exposure to Commercial Formulation Containing Deltamethrin and Cypermethrin Insecticides Impacts Redox System and Induces Unexpected Regional Effects in Rat Offspring Brain - Fatiha Mekircha; Donatella Fedeli; Cinzia Nasuti; Hadjer Kecies; Rosita Gabbianelli; Laura Bordoni (Antioxidants, 2023)
Several studies have shown that the oxidative impact of pesticides is most prevalent in rural environments where they are intensively used. At different levels, pyrethroids are reported to promote neurodegeneration; they share the ability to promote oxidative stress, and to induce mitochondrial impairments, α-synuclein overexpression and neuronal cell loss. The present study evaluates the impact of early-life exposure to a commercial formulation containing deltamethrin (DM) and cypermethrin (CYP) at a dose of 1/100 LD50 (1.28 and 2.5 mg/kg, respectively). Rats aged 30 days old, treated from the 6th to the 21st day of life, were tested for brain antioxidant activity and α-synuclein levels. Four regions of the brain were analyzed: the striatum, cerebellum, cortex and hippocampus. Our data demonstrated a significant increase in catalase (CAT), superoxide dismutase (SOD) and glutathione (GSH) antioxidant levels in the brain regions compared to the controls. Pups exhibited no significant changes in protein carbonyl levels and lipid peroxidation. Striatal α-synuclein expression was significantly reduced in the rats exposed to DM + CYP, while the treatment resulted in a non-significant increase in the other brain areas. These findings indicate unexpected effects of postnatal treatment with the commercial formulation containing DM and CYP on brain redox state and α-synuclein expression, suggesting an adaptive response.